Limiting hospital resources for acute appendicitis in children: Lessons learned from the U.S. epicenter of the COVID-19 pandemic()()() - Kvasnovsky, Charlotte L (J Pediatr Surg, 2021)
INTRODUCTION: The COVID-19 pandemic resulted in the suspension of nonemergent surgeries throughout New York. Our tertiary care children’s hospital pivoted towards a brief trial of intravenous (IV) antibiotic therapy in all patients in order to limit operating room (OR) utilization and avoid prolonged hospital stays. We describe our pandemic-based strategy for non-operative management (NOM) of appendicitis but with a limited duration of IV antibiotics. METHODS: We performed a retrospective study of children treated for acute appendicitis at our center from 3/31/2020 to 5/3/2020 during the peak of the New York pandemic. We compared appendicitis volume to similar months in prior years. We evaluated failure of NOM, length of stay, and compared characteristics of children we successfully treated with our expanded NOM protocol to previously published inclusion criteria for NOM. RESULTS: 45.5% of children (25/55) with acute appendicitis underwent NOM. Of the 30 who underwent surgery, 13 had complicated appendicitis while 17 had simple appendicitis. Three patients were COVID-positive, although none had respiratory symptoms. The majority of patients presenting with acute appendicitis (78.2%) did not meet previously published criteria for NOM. CONCLUSIONS: We treated a similar volume of children with acute appendicitis during the pandemic compared to prior years. We applied non-operative management to nearly half our patients, even as we expanded inclusion criteria for NOM to reduce OR utilization, but limited the duration of the antibiotic trial to avoid prolonged hospital stays. TYPE OF STUDY: Retrospective study. LEVEL OF EVIDENCE: IV.